-13-5x=7-9x

Simple and best practice solution for -13-5x=7-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13-5x=7-9x equation:


Simplifying
-13 + -5x = 7 + -9x

Solving
-13 + -5x = 7 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-13 + -5x + 9x = 7 + -9x + 9x

Combine like terms: -5x + 9x = 4x
-13 + 4x = 7 + -9x + 9x

Combine like terms: -9x + 9x = 0
-13 + 4x = 7 + 0
-13 + 4x = 7

Add '13' to each side of the equation.
-13 + 13 + 4x = 7 + 13

Combine like terms: -13 + 13 = 0
0 + 4x = 7 + 13
4x = 7 + 13

Combine like terms: 7 + 13 = 20
4x = 20

Divide each side by '4'.
x = 5

Simplifying
x = 5

See similar equations:

| 2x^2-9x-11=0 | | =2x+4x | | 5(7x-3)=10 | | -35-5x=4x+19 | | 4=0.167t-0.67 | | -2(w+6)+6w=4(w-3) | | 8-9x=66-23x | | 2(w+2)+w=3(w-1)+6 | | 6(y+1)-9=4(y-1)+2y | | 165-6x=5x+22 | | 2-3y=1 | | 16x^4-24x^2+9=0 | | -4(y+4)=3(y+4)+7 | | x+2-3x=-5x+8 | | 2(y-1)-3y=3(y-6) | | .6+.25x-.33=.75x | | 4(95-8x)=x-15 | | x+1=3x+3 | | 4(y+1)-7=3(y-1)+y | | x+1=x+3 | | -5x+6x-5=5x+4-5x | | 4y^2+12y+5=0 | | 12x-31=3x-4 | | 3a+2=-6-d | | .33+2=5 | | x^2-3xy+2y^2=4 | | 25=9x-74 | | x^2+5x-88= | | (n^6)-1=3 | | 7+x=19 | | 6x+10=363x | | 5(3x+1)=7(x+1) |

Equations solver categories